KARAKTER TOKOH UTAMA NOVEL RAHASIA SUNYI KARYA BRAHMANTO ANINDITO DAN RELEVANSINYA TERHADAP PEMBELAJARAN SASTRA SMA - Ratih Utami Ramadhaniati; Dewi Lestari; Sonia Apriliani Ratika Putri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2022)
Abstract The This study aims to describe how the main character in the novel Secrets of Silence by Brahmanto Anindito is. And its relevance to literary learning in high school. The formulation of the problem in this research is how is the main character in the novel Secret of Silence by Bramanto Anindito? How is it relevant to learning literature in high school? The method used in this study is a qualitative descriptive method. The data collection technique used is the documentation technique, while the data analysis technique is the literary work analysis technique. Based on the results of the study, it was found that in the novel Secret of Silence by Bramanto Anito, there were 11 (eleven) characters, namely the sea of ​​spaceman, Kirei Powler, Tiara Kristantina, Mr. Fowler, Lusi Therapyna, Randu, Uncle Inal, Aunt Ina, Randi and Roa. And the main character is Lautan Angkasawan who has an unyielding, responsible and brave character. The second main character is Kirey Fowler who has a kind, intelligent and introverted character. The novel Rasa Sunyi by Brahmanto Anindito also has relevance to literary learning in high school. Based on the results of the study, it can be concluded that the novel Rasa Sunyi by Bramanto Anindito has relevance to literary learning in high school based on its relationship with basic competence (KD) and linguistic aspects. The main character can also be used as a good character for the reader. Because there are so many positive sides.